An Update on Neurosurgical Management of Primary CNS Lymphoma in Immunocompetent Patients - Scheichel, Florian; Pinggera, Daniel; Popadic, Branko; Sherif, Camillo; Marhold, Franz; Freyschlag, Christian Franz (Frontiers in Oncology, 2022)
Primary central nervous system lymphoma (PCNSL) are rare CNS tumors that harbor a conspicuously longer diagnostic delay compared to other malignant brain tumors. The gold standard for diagnosis is stereotactic biopsy in order to acquire tissue for histopathological analysis and therefore neurosurgery plays a central role when reducing the diagnostic period is mandated. However, histopathological diagnosis could be complicated if the patient was preoperatively exposed to corticosteroids. Besides the histopathological result, diagnosis of a PCNSL also requires a full diagnostic workup to exclude cerebral metastatic disease of a systemic lymphoma. Most reviews on PCNSL discuss recent advancements of systemic treatment options from an (neuro-)oncologic point of view, whereas our intention was to discuss the optimization of the diagnostic period and therefore describing current standards of imaging, summarizing the diagnostic workup, discussing the surgical workup and future diagnostic prospects as well as the influence of preoperative corticosteroid therapy in order to reduce the diagnostic delay of PCNSL patients.